L’URSS et ses conceptions de sa sécurité : De brejnev à Andropov - Guerra, Adriano (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1984)
The international developments of the last few years have once more brought forth the traditional questions on the foreign policy of the USSR. The strong coming hack of the Soviet military on the political scène has revived the debate on the nature of the Soviet power and on the role played by the Army and its representatives. Since 1975, Soviet policy has been what can be considered as a "policy of response", aimed at protecting the recently acquired "new frontiers" and at preventing the United States from availing themselves of the internal problems existing in the USSR to change the status quo to their advantage. Increasingly, the Soviet government, in his multiple interventions in various regions of the world - and particularly in Afghanistan - is resorting to the militarization of her ancient and new frontiers. This line of action makes the Soviet policy more and more unpredictable and intensifies the risks of confrontation around the globe.